Connecting skills planning to provision - Centre for Researching Education & Labour (REAL); University of the Witwatersrand, Johannesburg (University of the Witwatersrand, Johannesburg, 2023)
Skills planning and development for the public sector are intrinsically linked to the state’s capacity to deliver on its social service and development mandates.
Keywords: Skills planning; Skills provision; Public sector professionalisation; South African Government; SDG-10: Reduced inequalities